Gendered Stereotyping in Career and Technical Education: The Lived Experience of Female Students - Kim Lorraine Smith; Junghwan Kim (Adult Education Research Conference, 2018)
This phenomenological study aims to explore the lived experience of gendered stereotyping in career and technical education from voices of female adult students.
Keywords: female; gendered serotyping; career and technical education